SYNERGISTIC DYNAMICS IN MULTIDISCIPLINARY HEALTHCARE: EXPLORING THE INTERPLAY OF NURSING AND ALLIED HEALTH PROFESSIONS - Adel Barrak Aldhaferi, Youssef Malhan Samihan Aldhafeeri, Fawaz Majed AliAlmutairi, Turki Mutlaq Al-Jumaili (Chelonian Research Foundation, 2022)
The healthcare industry relies on the collaborative efforts of various disciplines to provide comprehensive and high-quality patient care. This study explores the synergistic dynamics between nursing and allied health professions, focusing on the interplay of medical secretaries, radiology, pharmacy, and emergency practices in nursing-enhanced environments. A mixed-methods approach was employed, combining a systematic literature review, surveys, and focus group discussions to gain a comprehensive understanding of the topic. The systematic literature review identified 24 studies that met the inclusion criteria, highlighting the importance of effective collaboration and communication among the targeted specialties. The survey, completed by 156 healthcare professionals, revealed positive perceptions of the synergies between medical secretary, radiology, pharmacy, and emergency practices in nursing-enhanced environments. Focus group discussions with 32 participants provided insights into the benefits, facilitators, barriers, and strategies for successful implementation of cross-disciplinary care pathways. The findings suggest that fostering synergies between these specialties leads to improved patient outcomes, reduced healthcare costs, and enhanced quality of care. Key facilitators include shared decision-making, standardized protocols, and interprofessional education, while barriers include limited resources, divergent professional cultures, and communication breakdowns. Healthcare organizations should prioritize the development and implementation of cross-disciplinary care pathways to optimize patient care and outcomes. Future research should focus on examining the specific mechanisms through which these synergies lead to improved outcomes and investigating strategies for overcoming barriers to implementation. Keywords: nursing, allied health professions, multidisciplinary collaboration, care pathways, patient outcomes